Weightlessness and Cardiac Rhythm Disorders: Current Knowledge from Space Flight and Bed-Rest Studies - Caiani, Enrico G.; Martin-Yebra, Alba; Landreani, Federica; Bolea, Juan; Laguna, Pablo; Vaïda, Pierre (Frontiers in Astronomy and Space Sciences, 2016)
Isolated episodes of heart rhythm disorders have been reported during 40 years of space flight, triggering research to evaluate the risk of developing life-threatening arrhythmias induced by prolonged exposure to weightlessness. In fact, these events could compromise astronaut performance during exploratory missions, as well as pose at risk the astronaut health, due to limited options of care on board the International Space Station. Starting from original observations, this mini review will explore the latest research in this field, considering results obtained both during space flight and on Earth, the latter by simulating long-term exposure to microgravity by head-down bed rest maneuver in order to elicit cardiovascular deconditioning on normal volunteers.